SOCIO-POLITICAL ANALYSIS OF POLITICAL CULTURE SYSTEM - Anvarov Abdulrashid (International Journal of Business, Law and Political Science, 2024)
culture and political consciousness, particularly in relation to the impact of globalization and the role of youth in shaping the political landscape. Method: A qualitative, descriptive methodology is employed, analyzing theoretical frameworks from political science literature, with a focus on Almond and Verba’s political culture typology. The study incorporates a comparative analysis of political systems and case studies to explore the evolution of political culture in different societies. Results: The research identifies three types of political culture—parochial, subject, and participatory—highlighting their relevance to political stability and the development of civil society. Furthermore, the study reveals that globalization significantly influences political behavior, especially among youth in post-2000 societies, shaping their political consciousness and engagement. Novelty: The paper’s contribution lies in its exploration of the intersection between globalization and political culture, particularly in post-Soviet states, and its critical analysis of the role of youth in navigating political systems. The findings emphasize the importance of fostering political awareness and participation in the face of global political pressures.